1992
DOI: 10.1182/blood.v79.10.2701.bloodjournal79102701
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of p53 gene and their relation to disease progression in B- cell lymphoma

Abstract: The alteration of p53 tumor suppressor gene was studied in 48 patients with B-cell lymphoma. A sequential combined technique of polymerase chain reaction-mediated single-strand conformational polymorphism (PCR- SSCP) or reverse transcription (RT)-PCR-SSCP and direct sequencing were used as a simple and sensitive approach to analyze nucleotide changes. By these methods, we identified 8 missense point mutations and 2 codon deletions in 9 of the 48 patients. These mutations were located in or close to the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 0 publications
1
31
1
1
Order By: Relevance
“…In this study we used FISH to investigate the incidence of p53 deletions in 79 patients with NHL. We found that p53 deletion was an uncommon abnormality in patients with NHL; however, unlike previously published studies (Lo Coco et al, 1993;Sander et al, 1993;Ichikawa et al, 1992), we found no correlation between p53 deletions and poor prognosis.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In this study we used FISH to investigate the incidence of p53 deletions in 79 patients with NHL. We found that p53 deletion was an uncommon abnormality in patients with NHL; however, unlike previously published studies (Lo Coco et al, 1993;Sander et al, 1993;Ichikawa et al, 1992), we found no correlation between p53 deletions and poor prognosis.…”
contrasting
confidence: 99%
“…Because an intact p53 function is required for the cells to undergo apoptosis induced by radiation and chemotherapy, p53 alteration can mediate resistance to these treatment modalities (Chang et al, 1995). For patients with non-Hodgkin's lymphoma, p53 alterations have been reported to correlate with clinical tumour stage, disease progression and poor outcome (Lo Coco et al, 1993;Sander et al, 1994;Ichikawa et al, 1992).…”
mentioning
confidence: 99%
“…7 In the present series of NHL, exon 5 was the most common mutation site, accounting for seven of nine mutations (77%). In previous reports of NHL, either no predominant site for p53 mutation was apparent, 27,28 or there was a high prevalence in exons 6 and 7. 29,30 In the present series there were two cases (one DLBL and one ATL) that harbored double transversion mutations consisting of a missense mutation and a nonsense mutation.…”
Section: Discussionmentioning
confidence: 81%
“…3,27,28 p53 gene mutations are considered as a pejorative finding in post-transplant LPD. 3,29 Chetty et al 30 report a marked expression of bcl-2 while p53 is downregulated in adult posttransplant LPDs with high-grade histology. For Chetty et al, these findings help to differentiate polymorphic LPD from high-grade NHL in which they found, as we did in our series, a marked expression of p53 protein.…”
Section: Discussionmentioning
confidence: 99%